1991
DOI: 10.1093/jnci/83.13.932
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of Autologous Melanoma Cells by Tumor*Infiltrating Lymphocytes: Association With Clinical Response

Abstract: Tumor-infiltrating lymphocytes (TILs) can be grown in vitro in medium containing interleukin-2 (IL-2). In clinical trials at the Surgery Branch of the National Cancer Institute, patients with metastatic malignant melanomas were treated with IL-2 plus the adoptive transfer of autologous TILs. At the time of treatment, TILs were assayed for in vitro lysis of fresh autologous and allogeneic melanoma cells and Daudi cells. Patients were evaluated for clinical response 4-8 weeks later. Lysis of autologous tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 0 publications
4
67
0
1
Order By: Relevance
“…Although functionally suppressed in vivo, cultured populations often are enriched with activated T cells and demonstrate cytotoxicity for autologous tumor cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Clinical trials involving the adoptive transfer of TIL supported with IL-2 have demonstrated regression of metastatic disease in a proportion of patients with renal cancer and melanoma (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Although functionally suppressed in vivo, cultured populations often are enriched with activated T cells and demonstrate cytotoxicity for autologous tumor cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Clinical trials involving the adoptive transfer of TIL supported with IL-2 have demonstrated regression of metastatic disease in a proportion of patients with renal cancer and melanoma (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, two factors that were repeatedly reported to have a significant positive association to clinical response were short culture duration and telomere length (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…TILs have been shown to be capable of specifically eliminating tumour cells (Aebersold et al, 1991), but also to be rendered potentially nonfunctional due to tumour-induced immunosuppression (Finke et al, 1990). In a previous study, we hypothesised that EMAP-II might act in such an immunosuppressive role, by directly inducing apoptosis in mitogen-activated lymphocytes (Murray et al, 2004).…”
Section: Discussionmentioning
confidence: 99%